Edenville eaudiobook A novel. - Rebelein, Sam (HarperAudio, 2023)
An unsettling, immersive, and wildly entertaining debut novel from an exciting new voice in horror for fans of Paul Tremblay and Stephen Graham Jones. ""Edenville is a delightfully gooey blend of gothic, cosmic, folk and body horror churned by a sharp-bladed critique of academia.""— Lucy A. Snyder, Bram Stoker Award-winning author of Sister, Maiden, Monster After publishing his debut novel, The Shattered Man, to disappointing sales and reviews, Campbell P. Marion is struggling to find inspiration for a follow-up. When Edenville College invites him to join as a writer-in-residence, he's convinced that his bad luck has finally taken a turn. His girlfriend Quinn isn't so sure—she grew up near Edenville and has good reasons for not wanting to move back. Cam disregards her skepticism and accepts the job, with Quinn reluctantly following along. But there's something wrong in Edenville. Despite the charming old ladies milling about Main Street and picturesque sunflowers dotting the sidewalks, poison lurks beneath the surface. As a series of strange and ominous events escalate among Edenville and its residents, Cam and Quinn find themselves entangled in a dark and disturbing history. Told with equal parts horror and humor, Edenville explores the urban legends that fuel our nightmares and the ways in which ambition can overshadow our best instincts. Sam Rebelein is an exciting, sharp new voice, sure to terrify readers for years to come. "The mundane horrors of rural and academic living collide with pure cosmic weirdness in Sam Rebelein's Edenville. Not since Jason Pargin's John Dies at the End have I been so horrified and grossed out by a book...I could say more, but honestly, the less you know about this book, the better. A fantastic debut."— Todd Keisling, Bram Stoker Award-nominated author of Devil's Creek and Cold, Black & Infinite Supplemental enhancement PDF accompanies the audiobook.